PENGARUH PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN - Fadlillah, Fikri nur; Barokah, Siti; Kalidhamar, Gearintis Lintang; Ashshiddiqy, Hanif; Yulianti, Rita (House of Management and Business (HOMBIS) Journal, 2024)
This study aims to determine the effect of consumer behavior on purchasing decisions at the DIY in Gombong. This research is an associative research. The population in this study is the unknown number of consumers who have visited the DIY in Gombong (Unknown Population). The number of samples used in this study were 96 respondents. The data collection technique in this research is literature study, observation, interview, questionnaire / questionnaire. The results showed that there was a significant influence between consumer behavior variables (X) on purchasing decisions (Y) at the DIY in Gombong.